THE RELATIONSHIP BETWEEN GADGET USE AND NUTRITIONAL STATUS IN EARLY CHILDHOOD - Sofie Alawiyah; Diding Kelana Setiadi; Heri Ridwan (Buletin Veteriner Udayana, 2024)
The use of gadgets in early childhood has become an increasingly common phenomenon in modern society. With the advancement of technology, children are increasingly exposed to gadgets such as smartphones and tablets from an early age. This raises concerns about their impact on children's health and development, including their nutritional status. This study aims to evaluate the relationship between gadget use and nutritional status in early childhood. The research method used is quantitative correlational with a survey design. The population of this study consists of parents of early childhood children at TK Pembina Negeri Paseh and TK PGRI Sanggar Winaya Licin, where a sample of 75 respondents was selected using total sampling. Data were collected through a questionnaire specifically designed to measure gadget use and the nutritional status of early childhood children. Analysis was performed using univariate and bivariate statistical tests, as well as the Rank Spearman correlation test. The analysis results indicate that the majority of early childhood children use gadgets moderately (1-2 hours per day), with most respondents having good nutritional status. However, there is no significant relationship between gadget use and the nutritional status of early childhood with a significance value of 0.331 (p > 0.05) and with a Spearman correlation coefficient of -0.114. Thus, it can be concluded that gadget use does not have a significant impact on the nutritional status of young children in this research sample. Therefore, it is hoped that future research can explore more broadly other factors that have an impact on children's nutritional status.